ข้อขัดแย้งในเรื่องอำนาจหน้าที่ของศาลรัฐธรรมนูญและศาลปกครอง : ประสบการณ์จากการบังคับใช้รัฐธรรมนูญแห่งราชอาจักรไทย (พ.ศ.2540) - อภิชญา บุญกระพือ (จุฬาลงกรณ์มหาวิทยาลัย, 2007)
The purpose of this thesis is studying the jurisdiction of the Constitutional court and the Administrative court according to the Constitution of the Kingdom of Thailand (B.E 2540). This thesis would particularly identify the inspection of the exercise of state power under Thailand Constitution and the power to examine the operation of independent commission by instructing the provision of Thailand Constitution; the relevant law about the jurisdiction of the Constitutional Court and the Administrational Court; the official decision of the Constitutional Court and the official order and judgment of the Administrative Court. Besides, an essential inquiry is how the jurisdictional conflicts between the Constitutional Court and the Administrational Court exist. In researching and studying the jurisdiction of the Constitutional court and the Administrative court, the process of operating the case and the jurisdiction are entirely different. The Constitutional Court empowers to judge only the case that relevant to the provision under the Constitution where as the Administrative Court would generally empower to settle all disputes about administrative field. The jurisdictional conflicts between the Constitutional court and the Administrative court exists in many ways such as the power to inspecting the correction of constitutional and the problem about the power to examine the operation of independent commission. The main cause of the contradiction is the distinction of understanding which is different from the intention of the Constitution. For example, the Constitutional Court has interpreted the Constitutional Law in the way that overwhelmingly expands the scope of its jurisdiction. This overwhelmingly interpretation has also affected the jurisdiction of the Administrative Court which causes the problem in the operation of other courts because the decision of the Constitutional Court is the ultimate decision and has influenced all other courts and commissions. Furthermore, although the effective the Constitution of the Kingdom of Thailand B.E. 2550 has been attempted to resolve all those problems, it would still be the jurisdictional conflicts between the Constitutional Court and the Administrational Court as long as there is no the understanding of the jurisdiction of the Constitutional Court and the Administrational Court in the same way as it should be. Therefore, I would not present the method to revise the Thailand Constitution because the Constitution of the Kingdom of Thailand B.E. 2550 has certainly regulated about the jurisdiction of the Constitutional Court and the Administrative Court, but I would present to the empowered people to do comprehension about their own roles and power of duty. The problem as stated above would not exist if they understand their specific roles in the same way and maintain their duty with careful.